Learning Methods of Islamic Religious Education Teachers on Students with Developmental Impairments - Darmawati Darmawati; Sagaf S. Pettalongi; Mohammad Idhan (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC EDUCATION, 2019)
This study examines the learning methods of Islamic religious education in ABCD Muhammadiyah special schools Palu. The method used is a qualitative method with data collection techniques through observation, in-depth interviews, and the study of various written documents. The results of research studies on Islamic education in special schools mentally disabled ABCD Muhammadiyah shows that learning in extraordinary schools is done by using examples through direct demonstration to students. In the learning process, the teacher uses a more friendly humanistic approach so that students are eager to follow the learning process. Every day the teachers give various topics of Islamic religious education learning starting in the morning until after hours of study through various demonstration activities. Besides that learning is also done through demonstrations that are carried out together and repeatedly so that students easily practice it.